2016
DOI: 10.5194/isprs-archives-xlii-2-w1-89-2016
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Measurement Using Terrestrial Laser Scanner for Cultural Heritage

Abstract: ABSTRACT:Historical structures are one of the most essential element of cultural heritage. They reflect history, lifestyle and tradition of a country and society. However, they are damaged through the years due to human activities and natural hazards. Therefore, digital documentation of structures and monuments is critical for preservation, sustainability and protection of cultural heritage. Terrestrial laser scanner is a widespread used tool for obtaining 3D representation of real world. In this study, we aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…As the result, column was found to move from its preliminary position on 66 mm. Similar research is shown in [14], where the 386 years old historical mosque in Istanbul was chosen for the study due to the inclination of its minaret. The minaret was divided into 31 sections and for each section inclination values were calculated.…”
Section: A Case Study Of Deformation Measurements Of Istanbul Land Wamentioning
confidence: 92%
“…As the result, column was found to move from its preliminary position on 66 mm. Similar research is shown in [14], where the 386 years old historical mosque in Istanbul was chosen for the study due to the inclination of its minaret. The minaret was divided into 31 sections and for each section inclination values were calculated.…”
Section: A Case Study Of Deformation Measurements Of Istanbul Land Wamentioning
confidence: 92%
“…The need to filter out outliers arises from the fact that some of the points do not actually represent the analysed structure [6]. Those points appear as a result of the laser beam's reflection from other objects, of approaching the angular threshold of measurement, of the changes in the chimney surface albedo, or the local imperfections of the structure.…”
Section: Virtual Reference Pointsmentioning
confidence: 99%
“…Among its advantages, one should definitely point out the ease and speed of use (up to 1 million points per second); precision (up to mm level accuracy) with a high point density, noninvasive, and remote character of the measurement (also in very low light conditions); and the possibility of remote operation (especially important in life-threatening or healthendangering conditions). All these contribute to the fact that the TLS technique is now applied in as built surveys of buildings and structures for the purpose of documentation of their existing condition and checking compliance with the project [1][2][3][4]; creating the precise 3D models of structures of various types for design purposes [5]; documenting historical objects [6,7]; or destruction, deformation, and monitoring of engineering constructions and excavations [3,6,[8][9][10][11][12]; surveying of tunnels and rail tracks [13]; calculating volumes; applying building information modeling (BIM) [1,2]; monitoring the stability of the earth's structures [14]; and geotechnical and geological mapping in mining.…”
Section: Introductionmentioning
confidence: 99%
“…The latest advances in surveying technology, particularly that of 3D terrestrial laser scanning (TLS), give the opportunity to study damage and material decay using analysis of 3D point clouds generated by different instruments and techniques [2], [3]. Among them, TLS data are widely and successfully used for structural health monitoring in both civil engineering [4] and cultural heritage [5]. This paper focuses on detecting changes to a monument inflicted by climatic erosion, human activity, the spread of lichen, and the progress of archaeological excavations.…”
Section: Introductionmentioning
confidence: 99%